Genesis theology of creation : an exegetical study on Genesis 1:1-2:4a - Mangana, Melvin Moncada ([n.p.] : South East Asia Graduate School of Theology, 2000)
In the Old Testament, we started with the idea that God is the creator of the heavens and the earth. In the whole survey of the Bible, it shows that such recognition intertestamental and New Testament accounts.
The exegesis on Genesis 1:1-2:4a reveals that it is written in a latter period compared to the documents found in the writings of Isaiah and Jeremiah on the idea that God is creator.
A thesis submitted to the faculty of the South East Asia Graduate School of Theology.
In partial fulfillment of the requirements for the Degree of Master of theology.
Thesis (M. Theo.) - Iloilo City, Philippines
Keywords: Bible.O.T.--Genesis 1:1-2:4a